2017
DOI: 10.3390/molecules22040518
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Intramolecular Hydrogen Bonding in Levoglucosan Derivatives

Abstract: Organofluorine is a weak hydrogen-bond (HB) acceptor. Bernet et al. have demonstrated its capability to perturb OH···O intramolecular hydrogen bonds (IMHBs), using conformationally rigid carbohydrate scaffolds including levoglucosan derivatives. These investigations are supplemented here by experimental and theoretical studies involving six new levoglucosan derivatives, and complement the findings of Bernet et al. However, it is shown that conformational analysis is instrumental in interpreting the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…The two exceptions to this trend occur when M = Et and A = S or P. Overall, both the sign and magnitude of these changes are consistent with the formation of intramolecular hydrogen bonds in similar systems. [71,72] The same trends are observed in the M06-2X/aTZ and MP2/TZ NMR data reported in the Supplementary Material. However, it should be noted that changes NMR chemical shifts (often denoted Δδ) have the opposite sign as those associated with isotropic shielding constants (Δσ).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The two exceptions to this trend occur when M = Et and A = S or P. Overall, both the sign and magnitude of these changes are consistent with the formation of intramolecular hydrogen bonds in similar systems. [71,72] The same trends are observed in the M06-2X/aTZ and MP2/TZ NMR data reported in the Supplementary Material. However, it should be noted that changes NMR chemical shifts (often denoted Δδ) have the opposite sign as those associated with isotropic shielding constants (Δσ).…”
Section: Resultssupporting
confidence: 78%
“…The cis/trans energy difference for 2-fluoro and 2-chlorophenol were found to be slightly larger and on the order of 3 or 4 kcal mol −1 from DFT and MP2 computations [50], which is perhaps not surprising given that phenols are significantly more acidic than cyclopentanols. Subsequent analyses of these constrained intramolecular contacts based on the electron density, orbitals and/or electrostatic potential [64,65,66,67,68,69,70,71,72,73] are avoided in the present study because they have been shown to yield rather inconsistent results [34,48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a model of hydrogen bonding between the POSA fluorine atom and a polymer hydroxyl group is proposed in Figure D based on their proximity. Previous studies have shown O–H···F–C hydrogen bonds in various cases of small organic molecules and wide utilization of fluorine substituents for lead optimization in drug discovery …”
Section: Resultsmentioning
confidence: 99%
“…Quantum calculations are an important means to analyze interactions such as these and the influence of such calculations represents a common theme in much of the work described here. Quiquempoix et al look at levoglucosan and its derivatives [ 29 ], while variously substituted aminobenzamides come under the scrutiny of Mphahlele et al [ 30 ]. Mammino considers the relevance of these interactions to an antioxidant [ 31 ]; the possibility of multiple intramolecular H-bonds, and their relevance to regioisomers, is discussed by Martínez-Cifuentes et al [ 32 ].…”
mentioning
confidence: 99%